Pemberdayaan Masyarakat Miskin Terdampak Erupsi Raung Melalui Pendidikan Kecakapan Hidup: Empowering Communities Affected by the Raung Eruption Through Life Skills Education - Sofyan Hadi (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2016)
The Raung volcanic eruption in East Java has caused significant economic losses and new unemployment, particularly among poor farming communities whose livelihoods depend on damaged agricultural land. This disaster has not only disrupted material well-being but also triggered psychological distress, weakening social solidarity. Empowerment through life skills education is proposed as a strategic solution to restore both economic capacity and psychosocial resilience. This study aims to analyze the implementation of community empowerment for the poor affected by the Raung eruption using a life skills education approach. The method employed is a qualitative descriptive approach with data collection through interviews, observation, and documentation in Sumberjambe District. The findings reveal that empowerment was carried out through problem identification, action planning, program implementation, and evaluation. Life skills education included personal, social, thinking, and vocational skills, realized through deliberative education, networking, and appropriate technology development such as micro-hydro, biogas, and waste banks. The study concludes that life skills education effectively facilitates post-disaster recovery and community independence. Recommendations include strengthening local cadres and integrating appropriate technology into village development policies. Erupsi Gunung Raung di Jawa Timur telah menimbulkan kerugian ekonomi signifikan dan pengangguran baru, terutama pada masyarakat miskin petani yang menggantungkan hidup pada lahan pertanian rusak. Bencana ini tidak hanya mengganggu kesejahteraan material tetapi juga memicu tekanan psikologis dan melemahnya solidaritas sosial. Pemberdayaan melalui pendidikan kecakapan hidup diajukan sebagai solusi strategis untuk memulihkan kapasitas ekonomi sekaligus ketahanan psikososial. Penelitian ini bertujuan menganalisis implementasi pemberdayaan masyarakat miskin terdampak erupsi Raung dengan pendekatan pendidikan kecakapan hidup. Metode yang digunakan adalah deskriptif kualitatif melalui wawancara, observasi, dan dokumentasi di Kecamatan Sumberjambe. Temuan menunjukkan bahwa pemberdayaan dilakukan melalui tahap identifikasi masalah, perencanaan aksi, pelaksanaan program, dan evaluasi. Pendidikan kecakapan hidup mencakup kecakapan personal, sosial, berpikir, dan vokasional yang diwujudkan melalui pendidikan musyawarah, pengembangan jaringan, serta teknologi tepat guna seperti mikrohidro, biogas, dan bank sampah. Penelitian menyimpulkan bahwa pendidikan kecakapan hidup efektif memfasilitasi pemulihan pascabencana dan kemandirian masyarakat. Rekomendasi meliputi penguatan kader lokal dan integrasi teknologi tepat guna ke dalam kebijakan pembangunan desa.